Comparative law: - Port, Kenneth L. (Carolina Academic Press, 2003)
The Second Edition puts Japanese law in legal, historical, and cultural context. This text is a comprehensive analysis of Japanese law and legal process that traces the question of the role of law through various areas including constitutional law, contracts, criminal law, corporate law, human rights, administrative law, civil litigation, antitrust, and labor law.